Improving Student’s Critical Thinking Skill in Mathematics Through Geogebra-Based Flipped Learning During Pandemi Covid-19: an Experimental Study - Andriani, Tika; Ulya, Nuriya Hazma Arifatul; Alfiana, Tina Putri; Solicha, Shervina; Hafsari, Salsa Bila Ayustiana; Ishartono, Naufal (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang; Vol 6 No 1 (2022): Journal of Medives : Journal of Mathematics Education IKIP Veteran SemarangDO - 10.31331/medivesveteran.v6i1.1901, 2022)
w